Islamic Religious Education Teachers' Strategies in Improving Religious Character Education of Students in Class XI of MA At-Taqwa Putra Bekasi - Rahmansyah, Frendy; Arifin , Bustanul; Jauhari, Irmawan (Jaanur Elbarik Indonesia, 2025)
This study aims to explore the strategies of Islamic Religious Education teachers in fostering religious character among Grade XI students at MA At-Taqwa Putra Bekasi. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that Islamic Religious Education teachers develop comprehensive planning through the preparation of contextual teaching modules integrating Islamic values. The implementation involves habituation of religious practices such as prayer, Quran recitation, moral storytelling, and ethical classroom interactions. Evaluation is carried out holistically through behavioral observation, feedback from fellow teachers and parents, and continuous reflection. The study concludes that character education at MA At-Taqwa is effectively embedded through collaborative, reflective, and affective strategies aligned with students' sociocultural context. These findings contribute to the theoretical framework of value-based education and offer practical insights for curriculum developers and educators in Islamic schooling systems